Penggunaan KJR (Kartu dan Jurnal Refleksi) untuk Optimalisasi Pembelajaran Tematik Kurikulum 2013 di Kelas V SD Pesurungan Lor 2 Kota Tegal - Primanda, Astrinuari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research was carried out based on problems that occurred in thematic learning in 5th Grade SD Pesurungan Lor 2 Tegal City. Teachers have difficulty in teaching and evaluating learning outcomes. Students have difficulties to learn materials so that they hinder the learning process and are unable to master the competencies required in the Curriculum 2013. The purpose of the reasearch to: (1) innovate in optimizing the understanding of thematic learning materials in the Curriculum 2013; (2) to find out the understanding of 5th Grade students about the thematic learning materials for the Curriculum 2013; (3) to improve the thematic learning outcomes of 5th Grade students. This research uses Fishbone Analysis and GAP Analysis methods. The use of Reflection Cards is carried out by students every time they finish the thematic learning by writing down what has been learned and conveying the contents of the Reflection Card so that students can remember the previous material. The Reflection Journal is filled in by the teacher by paying attention to the results of the Reflection Card. The use of Reflection Cards and Journals has an effect on increasing students' understanding and learning outcomes.